SQUARE2: Spacecraft in QUAdrature for Solar Exploration—A Mission Concept for Synergetic Observations of the Sun and Heliosphere - Telloni, D. (Frontiers in Astronomy and Space Sciences, 2022)
SQUARE^2 is the acronym for Spacecraft in QUAdrature for solaR Exploration, and is a mission concept for multi-instrumental two-point observations of the Sun and its environment. It stems from the need to have two probes that are systematically in orbital configurations of interest, such as quadratures or radial alignments, in order to successfully address some science topics that joint measurements by different spacecraft, not specifically designed though to operate in synergy, can only partially solve. This perspective paper describes the mission profile that SQUARE^2$ should have in order to achieve a better understanding of how the Sun creates and controls the heliosphere. Specifically, the combined use of remote-sensing and in-situ instrumentation aboard the twin SQUARE^2 probes would allow the connection of the locally sampled solar-wind plasma flow with its coronal drivers and a proper investigation of solar wind evolution, dynamics, and transient events in the inner heliosphere. The potential impact of SQUARE^2 and the science topics covered by such a solar mission are here discussed.